Animal models of cartilage repair. Issue 4 (April 2014) - Cook, J. L.; Hung, C. T.; Kuroki, K.; Stoker, A. M.; Cook, C. R.; Pfeiffer, F. M.; Sherman, S. L.; Stannard, J. P.
Abstract : Cartilage repair in terms of replacement, or regeneration of damaged or diseased articular cartilage with functional tissue, is the 'holy grail' of joint surgery. A wide spectrum of strategies for cartilage repair currently exists and several of these techniques have been reported to be associated with successful clinical outcomes for appropriately selected indications. However, based on respective advantages, disadvantages, and limitations, no single strategy, or even combination of strategies, provides surgeons with viable options for attaining successful long-term outcomes in the majority of patients. As such, development of novel techniques and optimisation of current techniques need to be, and are, the focus of a great deal of research from the basic science level to clinical trials. Translational research that bridges scientific discoveries to clinical application involves the use of animal models in order to assess safety and efficacy for regulatory approval for human use. This review article provides an overview of animal models for cartilage repair. Cite this article: Bone Joint Res 2014;4:89–94.